Bioethical Aspects in Modern Cardiosurgery of Coronary Artery Disease - Rudenko, Serhii A.; Andrushchenko, Tetiana A.; Gogayeva, Olena K.; Kashchenko, Yurii V. (Ukrainian Journal of Cardiovascular Surgery, 2021)
The paper focuses on ethical issues, provides data on personality qualities and socio-ethical factors necessary for the professional activity of a cardiovascular surgeon. The aim. To identify the most relevant bioethical aspects, personality traits necessary for a cardiovascular surgeon to carry out his/her professional activities. Materials and methods. Analytical review of scientific publications was performed using the abstract database of scientific libraries, text database of medical and biological publications as well as analysis of observations of our own research works. Results. The main stages of development of surgical treatment of coronary artery disease in Ukraine are highlighted. Analysis of the basic bioethical aspects which take place in a profession of cardiovascular surgeon is carried out. Important personality traits which are necessary for professional activity in cardiac surgery are established. Ethical principles and problems that take place in modern cardiovascular surgery are analyzed. Autologous transplantation which takes place during reconstructive shunt surgery is emphasized. Conclusions. High-tech diagnostic and treatment technologies in cardiac surgery, their specificity, irreversibility of biomedical experience and certain event (intervention) to prolong life and improve health of the patient place new demands on the cardiac surgeon and require special responsibility. Today’s cardiac surgery requires not only high-tech skills in using modern methods of operations, responsibility, but also comprehensive support of aspects of biomedical ethics in the treatment of patients.